2011
DOI: 10.1308/003588411x581385
|View full text |Cite|
|
Sign up to set email alerts
|

A single institution experience with skin sparing mastectomy and immediate breast reconstruction

Abstract: According to the NHS Information Centre's Hospital Episode Statistics, 131,566 women in England were diagnosed with breast cancer in [2004][2005]. Of these, 16,838 underwent a mastectomy, of which only 1,623 (9.6%) benefited from a skin sparing approach. It is expected that almost all women who have been recommended a mastectomy will be offered reconstruction in the immediate setting or as a delayed procedure. Skin sparing mastectomies (SSMs) and immediate breast reconstruction (IBR) preserves the natural cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, the average weight of the residual breast tissue in SSM was found to be a mere 0.02% of the total removed tissue [ 3 14 ]. Additionally, Doddi et al [ 15 ] indicated that locoregional recurrence after IBR cannot be affected by inadequate excision alone, but it is more affected by other prognostic factors. Many previous reports found similar results to those in our study, demonstrating no difference between SSM or NSM and conventional mastectomies [ 8 9 11 12 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the average weight of the residual breast tissue in SSM was found to be a mere 0.02% of the total removed tissue [ 3 14 ]. Additionally, Doddi et al [ 15 ] indicated that locoregional recurrence after IBR cannot be affected by inadequate excision alone, but it is more affected by other prognostic factors. Many previous reports found similar results to those in our study, demonstrating no difference between SSM or NSM and conventional mastectomies [ 8 9 11 12 16 ].…”
Section: Discussionmentioning
confidence: 99%